Congruency, Achievement, and the Self Directed Search - Pichl, Hermi Ann; Clark, Andrew K. (Canadian Journal of Counselling and Psychotherapy, 2011)
Holland's construct of congruency and its relationship to level of academic achievement were tested through the Self Directed Search (SDS). The study was designed to validate the following theoretical assumptions made by Holland: a) individuals seek occupational environments consistent with their personal orientation; b) individuals experience greater success when personality and environment are in congruence. Students were administered the SDS and the resulting summary code was compared for congruency using Holland's Occupations Finder. Results indicated that subjects' programs were congruent with their SDS summary codes. Significant relationships were found between congruent and non-congruent frequencies, and between academic achievement and congruency.